Perpustakaan Desa Sebagai Upaya Untuk Meningkatkan Minat Baca Masyarakat Desa Ciasihan - Apriani, Risa; Shafira, Dea Andara; Mardliyyah, Aenatul (JURNAL KAJIAN ISLAM MODERN, 2023)
This research is motivated by a decrease in interest in reading which results in low knowledge, one of which is the unavailability of public facilities for reading. The purpose of research and implementation of the procurement of this Village Library is to increase public interest in reading. The method used in this study is a qualitative descriptive method with data collection techniques interview, observation, and documentation as well as using data analysis techniques, namely triangulation. The implementation of the Procurement of Community Reading Gardens is to make a village library through several stages, namely the preparation stage, the implementation stage, as well as the evaluation and follow-up stages.